Campus-based organizations and their perceived impacts on students of the College of Management - Advincula, Reynold; Barrios, Isidro III; Bulng, Oliver; Billones, Leonardo, Jr; Carnaje, Kariza; Tambasin, Ferdinand
The study dealt with the impact of campus-based organizations on UPV-CM students. A total of 90 respondents served as the primary source of data for the study. This sample size was determined using the Slovin formula; the number of respondents per year level was determined in consideration of equal representation. Questionnaires were used in gathering primary data. The researchers used the stratified random smapling method and the answers of the respondents were tallied and tabulated. students join campus-based organizations primary because they want to develop their personal skills and for educational support. The respondents perceive academic organizations to be the most beneficial to students. Students from all year levels are homogenous with this thought. students also recommend that campus organizations should engage in activities like outreach programs and interscholastic activities. UPV-CM students are inclined not only to academic activities but also to social activities like outreach programs. Ninety-four percent of the students believe that students should join campus-based organizations.